Pertimbangan Hakim dalam Penyelesaian Perceraian akibat Perselisihan dalam Keluarga di Mahkamah Syar’iyyah Kota Banda Aceh Tahun 2022-2024 - khairuzzazi; Alimuddin; Shabarullah (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
Divorce is considered the last resort when marriage can no longer achieve its purpose of establishing sakinah, mawaddah, and rahmah due to prolonged disputes. This study aims to examine and analyze the judicial considerations of the judges at Mahkamah Syar’iyah Banda Aceh in deciding divorce cases caused by family conflicts, as well as to identify the legal foundations underlying these rulings. This research employs a qualitative method with a juridical-normative approach, using three divorce rulings as samples, namely Decision Number 1/Pdt.G/2022/MS.Bna, Decision Number 71/Pdt.G/2023/MS.Bna, and Decision Number 345/Pdt.G/2024/MS.Bna. Primary data were obtained from official court rulings, while secondary data were derived from legal literature and statutory regulations. The findings reveal that the judges’ considerations are based on two main points: the breakdown of the household due to continuous disputes and failed reconciliation efforts, and the inability of spouses to fulfill their marital rights and obligations. Divorce is deemed valid when maintaining the marriage would result in greater harm. The legal basis applied includes Law No. 1 of 1974, Government Regulation No. 9 of 1975, the Compilation of Islamic Law, jurisprudence, and Islamic legal principles. Thus, divorce is viewed as a legal measure to prevent greater harm to the parties involved.